Game Innovation; Nglegena World for Elementary Students - Latif, Ahmad Rizqi Latif Oktavian; Gandi, Andrian Gandi Wijanarko; Fadloli, M Fadloli Al Hakim (Jurnal Sistem Cerdas, 2025)
The use of learning media, especially in the context of developing educational games, has a significant role in facilitating effective learning, especially in introducing abstract material concretely to students. Learning media helps students overcome learning obstacles, create innovative solutions, and increase interest and understanding of learning material. This development discusses the implementation of the Nglegena World educational game, which was developed using RPG Maker MV software, as an innovative alternative in learning Javanese. Nglegena World focuses on learning basic Javanese script, helping students understand the concept and use of Javanese script in an interactive and fun way. By involving teachers and students in the learning process, this game has a positive impact in improving teachers' teaching skills, diversifying learning methods, as well as students' interest, understanding and knowledge of Javanese language and Javanese script. Keywords: learning media, educational games, Nglegena World, Javanese language, Javanese script, RPG Maker MV, innovative learning.